STING-ΔN, a novel splice isoform of STING, modulates innate immunity and autophagy in response to DNA virus infection - Deng, Jian; Zheng, Sheng-Nan; Zhang, Jing; Li, Cheng-Hao; Li, Tao; Wang, Pei-Hui (Cell communication and signaling, 2025)
Stimulator of interferon (IFN) genes (STING) is a central adaptor protein in the cGAS-STING signaling pathway, orchestrating the production of type I interferons (IFNs) in response to cytosolic DNA detection, a crucial mechanism in antiviral defense. However, further investigation is needed to understand how post-transcriptional regulation, particularly alternative splicing, modulates STING activity. We identified a novel alternatively spliced isoform of STING, termed STING-∆N, resulting from exon 3 skipping. We examined STING-∆N expression in various human tissues and cell lines and assessed its role in cGAS-STING signaling using RT-qPCR, luciferase reporter assays, SDD-AGE, immunofluorescence, and immunoblot analysis. We evaluated the influence of STING-∆N on HSV-1 proliferation and STING-induced autophagy by viral plaque assay and immunoblotting. To unravel the mechanistic role of STING-∆N, we further investigated its interaction with STING, TBK1, and 2'3'-cGAMP and its effect on the STING-TBK1 complex using co-immunoprecipitation and 2'3'-cGAMP pull-down assay. STING-∆N shares an identical C-terminal sequence (aa 121-379) with STING but lacks a 120-amino acid N-terminal region encoding three conserved transmembrane (TM) domains. STING-∆N is expressed in various human tissues and cell lines. STING-∆N significantly suppressed IFN activation induced by cGAS, 2'3'-cGAMP, and STING. STING-∆N also reduced type I and III IFN induction in response to double-stranded DNA, HPV, and HSV-1. Additionally, STING-∆N promoted HSV-1 replication and inhibited STING-induced autophagy. Mechanistically, STING-∆N interacts with 2'3'-cGAMP, STING, and TBK1, sequestering their binding and disrupting the formation of the 2'3'-cGAMP-STING and STING-TBK1 complexes. STING-∆N acts as a potent negative regulator of the cGAS-STING pathway, revealing a previously unrecognized regulatory mechanism by which alternative splicing modulates immune responses to DNA viruses. These findings suggest that STING-∆N could be a promising therapeutic target for modulating immune responses in viral infections, autoimmune diseases, and cancer.